Nilai-Nilai Pendidikan Islam Multikultural Dalam Buku Panduan Pengembangan Projek Penguatan Profil Pelajar Pancasila - Nafi’ah, Zulfa Ulinnuha; Saifulah, Saifulah; Solikhudin, M. Anang (Impressive: Journal of Education, 2023)
The Guidebook for the Development of the Pancasila Student Profile Strengthening Project is one of the guidebooks for creating a Pancasila student profile. In implementing the Pancasila student profile project, many educators and school institutions have not implemented it, one of which is due to the lack of understanding of educators and school institutions regarding the project to strengthen Pancasila student profiles. The purpose of this study was to determine the values ​​of multicultural Islamic education in the guidebook for developing a project to strengthen the Pancasila student profile, using a library research approach, using content analysis and descriptive analysis. From the results of the study it was several dimensions of the Pancasila profile project there are multicultural educational values, namely first in the dimensions of faith, piety to God Almighty and noble character, there are Pluralistic Religious values, tolerance, democracy, justice and humanity. Second, in the global diversity dimension, there are Nationalist, Pluralist, Tolerance and Justice values. Finally, in the mutual cooperation dimension, there are values ​​of mutual help, humanism, pluralism and tolerance.